2023
DOI: 10.1099/ijsem.0.005748
|View full text |Cite
|
Sign up to set email alerts
|

Marinagarivorans cellulosilyticus sp. nov., a cellulolytic bacterium isolated from the deep-sea off Noma-misaki, Japan

Abstract: Cells from strain GE09T, isolated from an artificially immersed nanofibrous cellulose plate in the deep sea, were Gram-stain-negative, motile, aerobic cells that could grow with cellulose as their only nutrient. Strain GE09T was placed among members of Cellvibrionaceae , in the Gammaproteobacteria , with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…There is no doubt that these are only just a few of the actors in the degradation process. For example, a recent study showed that Cellvibrio japonicus was identified as having cellulose degradation activity and a source of new cellulase [ 58 , 59 ]. This implies that investigating the genetic potential of C. japonicus may result in the identification and development of novel, environmentally friendly techniques for cellulose breakdown, which are crucial for tackling environmental issues, which include waste management and the manufacture of biofuels.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that these are only just a few of the actors in the degradation process. For example, a recent study showed that Cellvibrio japonicus was identified as having cellulose degradation activity and a source of new cellulase [ 58 , 59 ]. This implies that investigating the genetic potential of C. japonicus may result in the identification and development of novel, environmentally friendly techniques for cellulose breakdown, which are crucial for tackling environmental issues, which include waste management and the manufacture of biofuels.…”
Section: Discussionmentioning
confidence: 99%